Predictive equation for incremental shuttle walk test in adolescents - Pinho, Tânia Maria Pereira de (2015)
Background: The incremental shuttle walk test (ISWT) is one of the most used measures to assess cardiorespiratory fitness in clinical and research settings. Reference equations to predict ISWT distance (ISWD) in different populations have been established. However, an equation for Portuguese adolescents is not available. Aim: This study aimed at developing a reference equation to predict the ISWD for Portuguese adolescents. Methods: Healthy adolescents aged 12–17 years old participated in this cross-sectional study. Participants’ socio-demographic (sex and age) and anthropometric (body mass index (BMI)) data were collected. Lung function was assessed through spirometry and quadriceps muscular strength (QMS) was recorded with a hand-held dynamometer. Physical activity level was scored with Physical Activity Index (PAI). The ISWT was performed twice as recommended. The best ISWD was used for descriptive and inferential analysis. Results: A total of 125 (56 male, 69 female; age 14.6±1.3 years old) participants with normal lung function (forced expiratory volume in one second=104.8±14.9% predicted) completed the assessment. According to PAI score, 54.4% (n=63) of the participants were moderately active and QMS mean was 20.7±6.8 kgf. Participants walked on average 1254.0±280.9 (760–2250 m) meters in the ISWT. A multiple regression model showed that sex, BMI, QMS and PAI were independent contributors to the ISWD, explaining 54% of the variability (p<0.05). The derived reference equation was: ISWD= 814.49 + (286.80 × sex) - (3.05 × BMI) + (8.83 × QMS) + (22.30 × PAI), sex: female=0, male=1. Conclusion: Sex, BMI, QMS and PAI score were found to be contributors to the ISWD predictive equation for adolescents, providing a simple reference to assess their cardiorespiratory fitness. The predictive equation is a valuable tool to interpret ISWT results obtained from paediatric populations, both healthy and with pathology.